Quality indicators for teacher education (National Assessment and Accreditation Council (NAAC) IN, 2007)
This document presents a background perspective to quality in teacher education and its assessment, along with a set of quality indicators with descriptors and other details under six key areas, viz., Curriculum Design and Planning; Curriculum Transaction and Evaluation; Research, Development and Extension; Infrastructure and Learning Resources; Student Support and Progression and Organization and Management.
Keywords: TEACHER TRAINING